Rational Design of Zinc/Zeolite Catalyst: Selective Formation of p‐Xylene from Methanol to Aromatics Reaction. (4th February 2022) - Wang, Ning; Li, Jing; Sun, Wenjing; Hou, Yilin; Zhang, Lan; Hu, Xiaomin; Yang, Yifeng; Chen, Xiao; Chen, Congmei; Chen, Biaohua; Qian, Weizhong
Abstract: The production of p‐ xylene from the methanol to aromatics (MTA) reaction is challenging. The catalytic stability, which is inversely proportional to the particle size of the zeolite, is not always compatible with p ‐xylene selectivity, which is inversely proportional to the external acid sites. In this study, based on a nano‐sized zeolite, we designed hollow triple‐shelled Zn/MFI single crystals using the ultra‐dilute liquid‐phase growth technique. The obtained composites possessed one ZSM‐5 layer (≈30 nm) in the middle and two silicalite‐1 layers (≈20 nm) epitaxially grown on two sides of ZSM‐5, which exhibited a considerably long lifetime (100 % methanol conversion >40 h) as well as an enhanced shape selectivity of p ‐xylene (>35 %) with a p ‐xylene/xylene ratio of ≈90 %. Importantly, using this sandwich‐like zeolite structure, we directly imaged the Zn species in the micropores of only the ZSM‐5 layer and further determined the specific structure and anchor location of the Zn species. Abstract : Hollow triple‐shelled Zn/MFI single crystals not only exhibit a significantly long lifetime but also an enhanced shape selectivity for p ‐xylene in the methanol to aromatics (MTA) reaction. The Zn species were directly imaged in the micropores of only the ZSM‐5 layer and the specific structure and anchor location of the Zn species was determined.